The charismatic movement in Sierra Leone (1980-2010): A Missio-historical Analysis in View of African Culture, Prosperity Gospel and Power Theology - Bangura, Joseph Bosco (Vrije Universiteit, 2013)
In the 1980s, a new era dawned upon the history of Christianity in Sierra Leone which saw the rise of the Charismatic Movement (CM) in the church scene. This emergence brought a new context that challenged the nature of church and pastoral ministry as it was carried out by traditional mainline churches. Even though at its founding, the CM benefitted from the pioneering work of interdenominational evangelistic organizations, the movement quickly carved out a ministry that resonated with the religious and cultural sensibilities of many people in Sierra Leone, particularly the young educated African urban élite who remain the core sociological constituency targeted by its evangelistic activities. However, the rise of the CM in the historical context of the 1980s, its critical response to crucial themes in Sierra Leone‟s (African) cultures, its adoption of prosperity theologies and its espousal of theologies that they believe can capacitate its followers with spiritual power has not received any sustained critical study. This is creating a gap in understanding the recent gains of Christianity in Sierra Leone, thereby limiting a deeper knowledge of the changing context of African church historiography and missiology. Nevertheless, by its demonstration of a contextualized ministry that appears to make sense to people, the CM has positioned itself to mediate a reshaping of the context in which the churches carry out pastoral ministries in Sierra Leone. This study assesses the historical context in which the CM arose and discusses the movement‟s specific approach to crucial issues in Sierra Leone's (African) cultures, as well as its appropriation of the themes of the prosperity gospel and power theology in its ministry praxis.
free